Development of a comprehensive mangrove quality index (MQI) in Matang Mangrove: Assessing mangrove ecosystem health. (July 2019) - Faridah-Hanum, I.; Yusoff, Fatimah M.; Fitrianto, A.; Ainuddin, Nuruddin A.; Gandaseca, Seca; Zaiton, S.; Norizah, K.; Nurhidayu, S.; Roslan, M.K.; Hakeem, Khalid R.; Shamsuddin, I.; Adnan, Ismail; et al.
Graphical abstract: Highlights: Mangrove Quality Index ( MQI ) reflects overall mangrove ecosystem status. MQI consisted of five major components considering ecosystems and socio-economy. Ten ecosystem and socio-economy metrics were selected for MQI development. MQI ranking from 1 (worst) to 5 (excellent) to reflect mangrove health status. Abstract: Mangroves are multi-functional ecosystems providing resource provisions and various ecosystem services, all of which are critical to the local livelihood and national economy. However, unsustainable anthropogenic activities continue to undermine the health of these ecosystems resulting in environmental adversities and declining resources. This study aimed to formulate a Mangrove Quality Index ( MQI ) which took into consideration the mangrove forest, contributing components of a mangrove forest, soil, surrounding marine ecosystem, hydrology and the socio-economic variables. Three major sites representing the least, moderately and most-disturbed mangrove ecosystems in Matang, Malaysia were selected. These areas were used to assess the contribution of 43 variables from five categories, namely, mangrove biotic integrity, mangrove soil, marine-mangrove, mangrove hydrology, and mangrove socio-economic factors. Two types of indices were developed to indicate the status of each category, 1) Mangrove Quality Index for a specific category ( MQISi ) and, 2) Overall MQI to reflect the overall health status of the ecosystem. The indices for the five different categories were Mangrove Biotic Integrity Index ( MQIS1 ), Mangrove Soil Index ( MQIS2 ), Marine-Mangrove Index ( MQIS3 ), Mangrove-Hydrology Index ( MQIS4 ) and Mangrove-Socio-economic Index ( MQIS5 ). Using Principle Component Analysis, ten variables representing all the five categories were selected to formulate the overall MQI . They are aboveground biomass, crab abundance, soil carbon, soil nitrogen, number of phytoplankton species, number of diatom species, dissolved oxygen, turbidity, education level, and time spent fishing. We developed the overall MQI based on the total score obtained from each category. The health status of mangroves is ranked from 1 to 5 viz. 1 (worst), 2 (bad), 3 (moderate), 4 (good), 5 (excellent). In the Matang Mangrove, the health status of the least disturbed area is ranked 5, moderate disturbed area is ranked 4, while the most disturbed area is ranked 2. The Normalized Difference Vegetation Index (NDVI) supported the overall MQI developed. The NDVI for the least disturbed area in Matang ranged from −0.689846 to 0.652204, for the moderately disturbed area, it ranged from −0.732508 to 0.638625, while the most disturbed area ranged from −0.916667 to 0.314991.